Mechanisms Driving Postgraduate Health and Social Science Students' Cultural Competence: An Integrated Systematic Review. (3rd May 2022) - Lie Ken Jie, Christopher; Finn, Yvonne F.; Bish, Melanie; Carlson, Elisabeth; Kumlien, Christine; Chan, E. Angela; Leung, Doris Y.L.
Abstract : Purpose: The COVID-19 pandemic revealed a global urgency to address health care provision disparities, which have largely been influenced by systematic racism in federal and state policies. The World Health Organization recommends educational institutions train clinicians in cultural competence (CC); however, the mechanisms and interacting social structures that influence individuals to achieve CC have received little attention. This review investigates how postgraduate health and social science education approaches CC and how it accomplishes (or not) its goals. Method: The authors used critical realism and Whittemore and Knafl's methods to conduct a systematic integrated review. Seven databases (MEDLINE, CINAHL, PsycINFO, Scopus, PubMed, Web of Science, and ERIC) were searched from 2000 to 2020 for original research studies. Inclusion criteria were: the use of the term "cultural competence" and/or any one of Campinha-Bacote's 5 CC factors, being about postgraduate health and/or social science students, and being about a postgraduate curriculum or a component of it. Thematic analysis was used to reveal the mechanisms and interacting social structures underlying CC. Results: Thirty-two studies were included and 2 approaches to CC (themes) were identified. The first theme was professionalized pedagogy, which had 2 subthemes: othering and labeling. The second theme was becoming culturally competent, which had 2 subthemes: a safe CC teaching environment and social interactions that cultivate reflexivity. Conclusions: CC conceptualizations in postgraduate health and social science education tend to view cultural differences as a problem and CC skills as a way to mitigate differences to enhance patient care. However, this generates a focus on the other, rather than a focus on the self. Future research should explore the extent to which insight, cognitive flexibility, and reflexivity, taught in safe teaching environments, are associated with increasing students' cultural safety, cultural humility, and CC.